Electrochemically assisted PCD tool surface conditioning technique for silicon micromachining. (1st January 2014) - Katahira, Kazutoshi; Nakamoto, Kazuo; Yamazaki, Kazuo; Ohmori, Hitoshi
The demand for micromachining methods for single-crystal silicon has been steadily increasing. Micro tools made of polycrystalline diamond (PCD) have considerable promise in this regard. However, the contamination of the PCD tool surface increases the frictional resistance during machining, leading to degradation of the surface integrity of the workpiece. In this study, the feasibility of surface conditioning using a specific electrochemical technique was investigated. The technique was found to be effective in removing the surface contamination without damage to the tool edges. The conditioning method proposed in this paper is expected to bring about excellent machining performance of micro PCD tools, such as longer tool life, lower machining load, and higher machined surface integrity.